Warehouse Receipt System: A Bibliometric Analysis - Septya Nurul Ayu Rahmawati; Muhamad Subhi Apriantoro (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to conduct a bibliometric analysis of Scopus-indexed publications on the Warehouse Receipt System (WRS), with a particular focus on mapping the intellectual structure and evaluating the characteristics of Scopus documents in this field. Methodology: A bibliometric approach was applied using publications indexed in the Scopus database related to the Warehouse Receipt System. Bibliometric indicators were used to analyze research performance, publication patterns, and knowledge development, as well as to examine interactions between science and technology within the WRS domain. Results: The analysis provides a comprehensive mapping of the WRS knowledge domain, revealing the structure of research themes, trends in scientific output, and the evolution of new knowledge in the field. The results highlight key areas of concentration as well as underexplored topics within WRS research. Applications/Originality/Value: This study offers a systematic overview of global WRS research and contributes original value by mapping its intellectual structure. The findings serve as a strategic reference for researchers and policymakers, particularly in identifying priority areas that require greater emphasis to support the future development of the Warehouse Receipt System (SRG).